2022
DOI: 10.3389/fendo.2022.869980
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism More Prevalent in Patients With Cardioembolic Stroke and Atrial Fibrillation

Abstract: BackgroundPrimary aldosteronism (PA) is the most common cause of secondary hypertension, and patients are at an increased risk of atrial fibrillation (AF) and stroke. We assessed the prevalence of PA in patients with recent stroke.MethodsWe recruited 300 patients admitted to an acute stroke unit with diagnosis of cerebrovascular accident (haemorrhagic/ischaemic) or transient ischaemic attack. Three months post-stroke, plasma renin and aldosterone were measured. Patients with an elevated aldosterone–renin ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Following title and abstract screening, 32 full text articles remained for screening. Three articles fulfilled eligibility criteria for inclusion ( Figure 1 ) ( 6 , 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following title and abstract screening, 32 full text articles remained for screening. Three articles fulfilled eligibility criteria for inclusion ( Figure 1 ) ( 6 , 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two single center studies, one from Singapore and the other from Japan, were cohort studies of patients admitted with stroke or TIA ( 6 , 15 ). The third, also a single center study undertaken in China, was a cross-sectional study in young adults with stroke or TIA ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Nguyen and colleagues performed PA testing among 300 consecutive patients with hemorrhagic or ischemic stroke and found overt PA in 30% of patients with hypertension and atrial fibrillation, as compared to 11.1% in the subgroup with treatment-resistant hypertension and 13.3% in those with hypertension and hypokalemia. [90] Another observational study found that overt PA was highly prevalent (42.5%) in participants with atrial fibrillation and no other identifiable causes of arrhythmia, such as structural heart defect or coronary artery disease, suggesting that overt PA might have led to atrial fibrillation in these patients. [91] Current guidelines do not yet endorse screening for PA in patients with atrial fibrillation.…”
Section: Other Conditions Associated With Pamentioning
confidence: 99%
“…Atrial fibrillation has emerged as one of the cardiovascular complications associated with PA. A meta-analysis found atrial fibrillation to be 3.52 times more likely in patients with overt PA than in those with primary hypertension [2]. Nguyen and colleagues performed PA testing among 300 consecutive patients with hemorrhagic or ischemic stroke and found overt PA in 30 % of patients with hypertension and atrial fibrillation, compared to 11.1 % in the subgroup with treatment-resistant hypertension and 13.3 % in those with hypertension and hypokalemia [90]. Another observational study found that overt PA was highly prevalent (42.5 %) in participants with atrial fibrillation and no other identifiable causes of arrhythmia, such as structural heart defect or coronary artery disease, suggesting that overt PA might have led to atrial fibrillation in these patients [91].…”
Section: Other Conditions Associated With Primary Aldosteronismmentioning
confidence: 99%